Synthesis of positively and negatively charged silver nanoparticles and their deposition on the surface of titanium. Issue 1 (February 2016) - Sharonova, A; Loza, K; Surmeneva, M; Surmenev, R; Prymak, O; Epple, M
Abstract: Bacterial infections related to dental implants are currently a significant complication. A good way to overcome this challenge is functionalization of implant surface with Ag nanoparticles (NPs) as antibacterial agent. This article aims at review the synthesis routes, size and electrical properties of AgNPs. Polyvinyl pyrrolidone (PVP) and polyethyleneimine (PEI) were used as stabilizers. Dynamic Light Scattering, Nanoparticle Tracking Analysis, X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDX) have been used to characterize the prepared AgNPs. Two types of NPs were synthesized in aqueous solutions: PVP-stabilized NPs with a diameter of the metallic core of 70 ± 20 nm, and negative charge of -20 mV, PEI-stabilized NPs with the size of the metallic core of 50 ± 20 nm and positive charge of +55 mV. According to SEM results, all the NPs have a spherical shape. Functionalization of the titanium substrate surface with PVP and PEI-stabilized AgNPs was carried out by dropping method. XRD patterns revealed that the AgNPs are crystalline with the crystallite size of 14 nm.